Measurement of the branching ratios Γ(Ds*+→Ds+π0)/ Γ(Ds*+→Ds+γ) and Γ(D*0→D0π0)/ Γ(D*0→D0γ) - Aubert, B; Barate, R; Boutigny, D; Couderc, F; Karyotakis, Y; Lees, J; Poireau, V; Tisserand, V; Zghiche, A; Grauges, E; Palano, A; Pappagallo, M; et al. (2005)
Data samples corresponding to the isospin-violating decay Ds*+→Ds+π0 and the decays Ds*+→Ds+γ, D*0→D0π0 and D*0→D0γ are reconstructed using 90.4 fb-1 of data recorded by the BABAR detector at the PEP-II asymmetric-energy e+e- collider. The following branching ratios are extracted: Γ(Ds*+→Ds+π0)/Γ(Ds*+→Ds+γ)=0. 062±0.005(stat.)±0.006(syst.) and Γ(D*0→D0π0)/ Γ(D*0→D0γ)=1.74±0.02(stat.)±0.13(syst.). Both measurements represent significant improvements over present world averages. © 2005 The American Physical Society.